2021
DOI: 10.1038/s41598-021-93124-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subtypes of anticancer peptides based on sequential features and physicochemical properties

Abstract: Anticancer peptides (ACPs) are a kind of bioactive peptides which could be used as a novel type of anticancer drug that has several advantages over chemistry-based drug, including high specificity, strong tumor penetration capacity, and low toxicity to normal cells. As the number of experimentally verified bioactive peptides has increased significantly, various of in silico approaches are imperative for investigating the characteristics of ACPs. However, the lack of methods for investigating the differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Generally, they are selective in their interactions with cellular targets, do not accumulate to toxic levels in organs, and can be easily synthesized or/and modified. Their therapeutic potential as anticancer peptides (ACPs) or antiviral peptides (AVPs) has been extensively explored, frequently with the application of computational screening techniques [ 46 , 50 , 51 , 52 , 53 ]. It was found that due to negatively charged components on the surface of the cancer cell, anticancer peptides should contain cationic amino acid residues (Lys or/and Arg) to facilitate the electrostatic interaction with the cell [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, they are selective in their interactions with cellular targets, do not accumulate to toxic levels in organs, and can be easily synthesized or/and modified. Their therapeutic potential as anticancer peptides (ACPs) or antiviral peptides (AVPs) has been extensively explored, frequently with the application of computational screening techniques [ 46 , 50 , 51 , 52 , 53 ]. It was found that due to negatively charged components on the surface of the cancer cell, anticancer peptides should contain cationic amino acid residues (Lys or/and Arg) to facilitate the electrostatic interaction with the cell [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in ACPs, Gly, Lys, and Leu were found to be the dominant components. The activity against cancer cells can also be enhanced by the presence of Pro, Phe, and Tyr [ 53 , 55 ]. Hydrophobic residues and their modifications belong to the main components of several known anticancer cyanobacterial peptide-like structures such as dolastatin-10 [ 56 ], apratoxins [ 57 ], cryptophycins [ 58 ], aurilides [ 59 ], and belamide A [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological activity of food-derived peptides, including activity against cancer cells, is determined by their structural characteristics, such as amino acid composition, sequence, length, and total charge/hydrophobicity. Most food-derived anticancer peptides contain short amino acid sequences with residues ranging from 3 to 25 [ 29 ] or even longer [ 30 ], although peptides of lower molecular weight seem to have higher cytotoxicity [ 31 ]. In this study, the identified peptide sequences had a chain length of 7–37 amino acids, with the largest portion of fragments having 13–16 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of ACPs are affected by the composition of amino acids and their structure [ 18 ]. In the reported ACP databases (from ACP-DL, ACPP, ACPred-FL, AntiCP, iACP, CancerPPD, APD3, and SATPdb) [ 98 , 99 , 100 ], positively charged or hydrophobic amino acids (Gly, Ala, Phe, His, Lys, Leu, and Trp) have been highly observed in ACPs, compared to non-ACPs [ 46 , 101 ]. Especially, the positively charged amino acid, Lys, was frequently observed in ACPs, whereas the frequencies of negatively charged amino acids, Asp and Glu, were less than other amino acids in 1390 ACPs database analysis [ 101 ].…”
Section: Development Of Therapeutic Acpsmentioning
confidence: 99%